RELATIONSHIP BETWEEN ENTREPRENEURIAL INTENTION AND KNOWLEDGE ACQUSITION THROUGH THE SYSTEMATIC MAPPING STUDY (SMS) METHOD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The purpose of this paper is to map the context of the study on entrepreneurial intention that related to the context of knowledge acquisition studies by tracing the results of existing studies so that the research focus, research subject, type of research, country of study and research trends in the last 10 years can be found. This study uses a systematic mapping studies (SMS) method. The mapping strategy was carried out by tracing 3 electronic journal databases, namely Scopus, ScienceDirect and Emerald, which produced 49 relevant paper after going through the inclusion, exclusion and screening processes. The findings on the mapping from this SMS will be able to help other researchers to plan further research, because this research has the potential to find research gaps. The results of this study found that there are still several research studies that have the potential to become novelty and make new contributions to entrepreneurial intention and knowledge acquisition research. Researches with the mix method and case study methods are still few used, besides that there are some gaps or research gaps, for example research with the type of solution proposal research using qualitative methods has not been carried out, as well as the type of evaluation research using quantitative research methods not been carried out either.